Sense and sensibility - West, Clare; Austen, Jane, 1775-1817. (Oxford : Oxford University Press, 2008)
"Sometimes the Dashwood girls do not seem like sisters. Elinor is all calmness and reason, and can be relied upon for practical, common sense opinions. Marianne, on the other hand, is all sensibility, full of passionate and romantic feeling. She has no time for dull common sense - or for middle-aged men of thirty-five, long past the age of marriage. True love can only be felt by the young, of course. And if your heart is broken at the age of seventeen, how can you expect ever to recover from the passionate misery that fills your life, waking and sleeping?" --Back cover
Keywords: Readers (Adult); Reading comprehension -- Problems, exercises, etc; English language -- Textbooks for foreign speakers; High interest-low vocabulary books; Inheritance and succession -- Fiction; Social classes -- Fiction; Young women -- Fiction; Sisters -- Fiction; Domestic fiction